2011
DOI: 10.1016/j.adolescence.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and discrimination experiences among Korean‐American adolescents

Abstract: The bullying experiences of Korean‐American adolescents (N = 295) were explored in relation to discrimination and mental health outcomes. Bullying experiences were assessed by the Bully Survey (Swearer, 2005), discrimination by the Perceived Ethnic and Racial Discrimination Scale (Way, 1997) and depression by the Center for Epidemiological Studies – Depression Scale (CES‐D). Those who reported being bullied (31.5%) as well as those who reported both being bullied and bullying others (15.9%) experienced a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 33 publications
6
88
2
1
Order By: Relevance
“…Also, when participants perceived racial discrimination with a high level of stress, they were more likely to use substances. Previous studies reported that racial discrimination was associated with mental health problems among Asian Americans (Checn, Szalacha, & Menon, 2014;Fisher et al, 2000;Grossman & Liang, 2008;Juang & Cookston, 2009;Shin et al, 2011). Several studies reported that perceived discrimination was related to substance use among Asian American adults and adolescents (Chae et al, 2008;Chen at al., 2014;Park, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, when participants perceived racial discrimination with a high level of stress, they were more likely to use substances. Previous studies reported that racial discrimination was associated with mental health problems among Asian Americans (Checn, Szalacha, & Menon, 2014;Fisher et al, 2000;Grossman & Liang, 2008;Juang & Cookston, 2009;Shin et al, 2011). Several studies reported that perceived discrimination was related to substance use among Asian American adults and adolescents (Chae et al, 2008;Chen at al., 2014;Park, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although experiencing racial discrimination is a common stressor among Asian American adolescents, this group was left out of the mainstream of discrimination-related research until the late 1990s (Fisher, Wallace, & Fenton, 2000). Several studies reported perceived racial discrimination as associated with distress and depressive symptoms among minority adolescents (Fisher et al, 2000;Grossman & Liang, 2008;Juang & Cookston, 2009;Shin et al, 2011). However, the association between perceived racial discrimination and substance use particularly among Korean American adolescents is not clear because the association has not been well-studied in more recent times.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study examined the experiences of Korean-American adolescents who engaged in bullying in terms of moral disengagement and discrimination. Other bullying experiences among Korean-American adolescents, including the victims, have been reported in a previous study (22). In the 2011 study, Shin et al (22) also assessed discrimination experiences of Korean-American high school students in relation to bullying.…”
Section: Discrimination Experiences Among Korean-americansmentioning
confidence: 96%
“…Shin, D'Antonio, Son, Kim, & Park (2011), in an investigation of the relationship between bullying experience and depressive symptoms of 295 Korean American adolescents, found that those who experienced being bullied and those who experienced both being bullied and bullying reported levels of depression above the clinical cut-off score of 16 (M = 18.0 -19.3). Kim and Cain (2008), in their study of parenting and depressive symptoms of 56 Korean American adolescents, found that about 40% of the participants had clinically meaningful depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%